On Schur classes for modules over group rings - Semko, N. N.; Chupordya, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider the problem of the coupling between a factor-module A / C_A(G) and a submodule A(ω RG), where G is a group, R is a ring, and A is an RG-module. It is possible to consider C_A (G) as an analog of the center of the group and the submodule A(ω RG) as an analog of the derived subgroup of the group.